ANALYSIS OF THE EFFECT OF TROPICAL CYCLONE ON PM2.5 CONCENTRATION IN JAVA AND BALI (CASE STUDY : CYCLONE CHARLOTTE) - Faiq Tarikh, Mohammad
Weather and climate play a huge role in controlling air quality. Previous research had shown Tropical cyclones to be one of the meteorological phenomena that have a major influence on air quality, especially on PM2.5 concentrations. Indonesia as a country located around the equator is a region that is often indirectly affected by tropical cyclones. Tropical Cyclone Charlotte, which occurred in March 2022, is known to form an area of wind convergence that extends from the Indian Ocean around the south of Bali to West Java, thus affecting the weather system of Java and Bali. This study will examine how Tropical Cyclone Charlotte in each phase affects changes in PM2.5 concentrations in Java and Bali, represented by four major cities, such as Bandung, Yogyakarta, Surabaya and Denpasar. This study used data from the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA5 to analyze atmospheric conditions during the event of Cyclone Charlotte by looking at several parameters, such as temperature, mean sea level pressure, surface wind, and wind at level 925 hPa. In addition, it also uses hourly PM2.5 observation data from Nafas Indonesia and the best track data of Cyclone Charlotte issued by the Bureau of Meteorology, Australia. In phase I, it tends to decrease PM2.5 in areas close to the cyclone location (Yogyakarta and Denpasar), but tends to increase PM2.5 in areas far from the cyclone location (Bandung). In phase II, it tends to decrease PM2.5 in the four cities, while Surabaya tends to have no change in phase I and II. In phase III, it tends to increase PM2.5 in areas close to the cyclone location (Yogyakarta, Surabaya and Denpasar), but tends to decrease PM2.5 in areas far from the cyclone location (Bandung). In phase IV there was a very significant increase in PM2.5 in all four cities.